2016
DOI: 10.1371/journal.pone.0164398
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Birth Characteristics and Childhood Embryonal Solid Tumors: A Population-Based Report from Brazil

Abstract: BackgroundSeveral maternal and birth characteristics have been reported to be associated with an increased risk of many childhood cancers. Our goal was to evaluate the risk of childhood embryonal solid tumors in relation to pre- and perinatal characteristics.MethodsA case-cohort study was performed using two population-based datasets, which were linked through R software. Tumors were classified as central nervous system (CNS) or non-CNS-embryonal (retinoblastoma, neuroblastoma, renal tumors, germ cell tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The observed overall increase in incidence of approximately 1% per year was documented in other studies over several decades, and decelerated recently in high-income settings ( 29 , 30 ). The modestly growing incidence rates may indicate changes in exposures, such as changing maternal and birth characteristics ( 31 ), or environmental risk factors ( 2 ). Nevertheless, improvements in the capacity to diagnose childhood cancer may have contributed to the increasing incidence of the CNS neoplasms, as diagnostic computed tomography and magnetic resonance imaging technology was introduced progressively in LAC during the study period ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed overall increase in incidence of approximately 1% per year was documented in other studies over several decades, and decelerated recently in high-income settings ( 29 , 30 ). The modestly growing incidence rates may indicate changes in exposures, such as changing maternal and birth characteristics ( 31 ), or environmental risk factors ( 2 ). Nevertheless, improvements in the capacity to diagnose childhood cancer may have contributed to the increasing incidence of the CNS neoplasms, as diagnostic computed tomography and magnetic resonance imaging technology was introduced progressively in LAC during the study period ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of characteristics at birth by caesarean, operative vaginal and spontaneous vaginal birth found that caesarean birth was associated with embryonal solid tumours after 2 years but not beforehand. 5 Similarly, a case-control study of 12 539 children suggested that caesarean birth was associated with the risk of neuroblastoma after 18 months of age only. 3 In contrast, a study of 5081 cases and 18 927 controls found that caesarean section was associated with the risk of acute lymphoblastic leukaemia between 2 and 4 years, but not at earlier or older ages.…”
Section: Ta B L Ementioning
confidence: 99%
“…1 The causes of most childhood cancers are poorly understood, but the young age of onset has led to the hypothesis that perinatal exposures including mode of delivery may be involved. [2][3][4][5] Caesarean section is linked with the risk of childhood cancer through the hygiene hypothesis. [6][7][8] Under the hygiene hypothesis, children born by caesarean bypass the birth canal and have reduced exposure to maternal vaginal and intestinal flora.…”
mentioning
confidence: 99%
“…Around 40% of all pediatric cancers account to solid tumors (Table 2) [28]. Many of them are so-called embryonal tumors, a heterogeneous group of cancers that exhibit in common a developmental origin from undifferentiated cells, and present histological features that resemble the forming fetus tissues [29]. Their genesis is likely based on arrest and/or defects in cellular pathways involved in cell growth and differentiation during pre-and post-natal periods, which result in retention of either embryonal or fetal tissue characteristics [30].…”
Section: Embryonal Solid Tumorsmentioning
confidence: 99%
“…It is worth stating that high resolution magic angle spinning (HR-MAS) sample size can vary from 12 µL to 50 µL (depends on rotor that was used) and usually are around 15 mg [21] or 60 mg for the 4 mm rotors, liquid samples' size varies from 250 to 500 µL, and cancer cell lines usually report preparation procedures starting from 10 6 to 10 9 cells per sample for 4 mm 50 µL rotors. Some articles explored the small number of individuals because of the rarity of embryonal solid tumors, such as 5-15 samples, while cohorts with a greater number of individuals counted on 90-250 samples [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Metabolomics On Embryonal Solid Tumorsmentioning
confidence: 99%